THE IMPORTANCE OF ATHLETICS IN PHYSICAL ACTIVITY AND THE RULES OF DOING IT - Bakhadir Abbasov Asatillayevich (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides information about athletics, running short distances in athletics classes, types of athletics and their rules.